Sistas : [videorecording (DVD)] the musical - Battle, Hinton; Tomosunas, Eric; Ferrone, Kenneth; Marcic, Dorothy; Fouche, Jennifer; Lee, Tracey Conyer; Rhoades, Lexi; Nixon, April; Goldberger, Amy (RLJ Entertainment, 2013)
After their grandmother's death, five female relatives gather in her attic to pick a song for her funeral and they are reminded of their African-American history through popular music across the decades.